Cystatin C Serum Level and the Severity of Preeclampsia - Winarto, Abraham; Suparman, Eddy; Wantania, John (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: Determining the cystatin C serum level among normotensive, mild preeclamptic, severe preeclamptic pregnant women and their relationship with the severity of preeclampsia. Method: The study was held using cross sectional design in Prof. Dr. RD Kandou Hospital in Manado and its network hospitals. We did on 51 samples at term pregnant women, consisting of 17 samples for each group in normotensive, mild preeclampsia, and severe preeclampsia. The data were analyzed using SPSS version 22.0 software through ANOVA and Kruskal Wallis statistical test. Result: The mean cystatin C serum concentration in normotensive pregnant women, mild preeclampsia, and severe preeclampsia were 0.82 mg/l, 1.03 mg/l, and 1.32 mg/l; respectively. The ANOVA statistical test showed the significant association between cystatin C level and severity of preeclampsia (p